Water Quality and Pollution Level in Plawangan Barat, Segara Anakan, Cilacap Based on Pollution Index Approach - Hidayati, Nuning Vita; Kartikaputri, Ariani Dian; Hernayanti, Hernayanti; Mahdiana, Arif (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2023)
Segara Anakan is a lagoon located in Cilacap, Central Java. It is characterized as a fragile ecosystem that is very susceptible to the impacts of alterations and land development. This region is susceptible to habitat degradation caused by human activity, resulting in alterations in water quality and pollution. The objective of this study was to provide a comprehensive description of water quality by analysing its physical and chemical properties. Additionally, the study intended to assess the level of water pollution by employing the Nemerow Sumitomo Pollution Index (PI) approach. The water quality sampling was conducted in the western region of Segara Anakan, namely Plawangan Barat. The obtained data were compared to the established standard quality for marine organisms, as outlined in the PP RI No. 22/2021. The classification of the water pollution level was determined according to Minister of Environment Decree No. 115/2003. The findings of this study indicate that the parameters of temperature, salinity, pH, dissolved oxygen (DO), and biological oxygen demand (BOD) in the water remain suitable for marine life throughout all study stations. However, it was observed that the levels of Total Suspended Solid (TSS), phosphate, and nitrate did not match the established safety thresholds. The pollution index indicated that the water quality in West Plawangan shows varying pollution levels, ranging from light to moderate pollution. Based on the findings obtained, it can be concluded that the Segara Anakan lagoon exhibits a diminished level of suitability for the life of marine organisms.Keywords: Water Quality, Index PI, Nemerow Sumitomo, Plawangan Barat, Marine Pollution